Integration of Spirituality, Values and Ethics in Leadership Practice and Theory in Egypt - Ahmed, Abubakar (International Journal of Leadership and Governance, 2024)
Purpose: The aim of the study was to investigate the integration of spirituality, values, and ethics in leadership practice and theory. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Integration of spirituality, values, and ethics in leadership practice and theory in Egypt shows a strong emphasis on Islamic principles and teachings. Leaders often draw upon religious values to guide their decision-making and ethical behavior. This integration fosters a sense of moral responsibility and accountability among leaders, promoting ethical leadership practices. However, there is also a need for a balance between religious principles and modern leadership theories to ensure inclusive and effective leadership. Unique Contribution to Theory, Practice and Policy: Social network theory, Graph theory & Complex systems theory may be used to anchor future studies on the integration of spirituality, values, and ethics in leadership practice and theory. Design and implement leadership development programs that explicitly incorporate components related to spirituality, values, and ethics. Advocate for the implementation of policies and regulations that institutionalize ethical standards within organizations and industries.